2020
DOI: 10.17756/jfcn.2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Food Waste: Challenges and Opportunities

Abstract: Food waste is a global challenge from collection to disposal. The problem associated with food waste is on the increase ranging from its discharged, lost, degradation and contamination. Food wastage can be effectively managed through proper storage, purchasing what is needed and giving excess to those in need. The most effective means of managing food waste is through effective sorting at source and recycling for industrial processes for the production of valueadded products, thereby reducing the options of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Biowastes are a group of municipal wastes, whose mass has recently increased significantly. The prevailing pandemic situation following the COVID-19 outbreak favors such a trend, which was confirmed by numerous authors [1][2][3]. According to the cited authors, the mass of generated biowastes has increased by 20%, while even a 1.5-fold increase in the mass was noted in some areas.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Biowastes are a group of municipal wastes, whose mass has recently increased significantly. The prevailing pandemic situation following the COVID-19 outbreak favors such a trend, which was confirmed by numerous authors [1][2][3]. According to the cited authors, the mass of generated biowastes has increased by 20%, while even a 1.5-fold increase in the mass was noted in some areas.…”
Section: Introductionmentioning
confidence: 78%
“…The reasons include primarily the increased consumption and the shopping panic accompanying the imposed lockdown and the resulting fear of problems with the supply of food products. First of all, some products were excessively accumulated, often being perishable food products with a short shelf life, which have not been fully used and constituted a source of food waste, followed by an additional mass of biowaste [2]. Jribi et al [4] reported that this type of biowaste comprises mainly vegetables, fruit and cereal products, which were either inappropriately stored or were inadequately prepared and had to be disposed of.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Canada, the Second Harvest Food Rescue App connects businesses with surplus food to social organizations (about 2300 organizations) distributing surplus food to reduce FW . Consumers could play a key role in lowering FW at household levels by well-planned purchases and adopting adequate storage. , In addition, sorting of FW at sources is known to be an effective way to divert some of the wasted food either for redistribution or for use as animal feed, which thus can be useful in reducing the generation of FW. Various policy initiatives have also been deployed to reduce FW from the food chain.…”
Section: Food Waste Reduction Initiativesmentioning
confidence: 99%
“…production while in developing countries about a hundred kilograms of food per person per annum is wasted at the consumption stage (Makanjuola et al, 2020: Haley et al, 2021Music et al, 2021). In the European Union, food waste was defined as any food substance, raw, cooked, that is discarded since 1975 until 2000 (Porpino, 2016).…”
mentioning
confidence: 99%
“…Akerele et al (2017) estimated that almost 3-7% of food equivalent to ₦1500 per month is wasted by household in Nigeria. Almost 123 million metric tons of food is wasted yearly in Nigeria before reaching the market (Makanjuola et al, 2020). It was reported that about 1.3 billion metric tonnes of food is wasted in Nigeria due to poor or inadequate storage facilities (Adedayo et al, 2020).…”
mentioning
confidence: 99%